Expressive Speech Acts as Reflections of Educational Leadership and Management Values in Habiburrahman El Shirazy’s Kembara Rindu: A Pragmatic Perspective - A. Tenriawaru Atmarani; Muh Hasbi; Aslan Abidin (Al-Qalam Institue, 2025)
This study aims to examine expressive speech acts in Habiburrahman El Shirazy’s novel Kembara Rindu and to explore how these speech acts reflect educational leadership and management values within socio-religious contexts. Using a qualitative descriptive approach, the study adopts a pragmatic framework grounded in Speech Act Theory to analyze selected character dialogues. The data consist of utterances expressing gratitude, apology, praise, complaint, lamentation, and religious wishes, which are examined to identify their types and pragmatic functions within the narrative. The findings reveal that expressive speech acts are predominantly employed to maintain interpersonal harmony, reinforce moral positioning, and construct religious identity. Moreover, these expressive acts function as strategic linguistic tools that reflect core dimensions of educational management, including value-based leadership, ethical communication, emotional regulation, and character formation. Rather than serving merely as emotional expressions, the speech acts demonstrate how language operates as a managerial instrument for guiding behavior, managing social relations, and transmitting educational values. This study implies that literary texts can serve as reflective resources for educational management by illustrating effective communication practices and moral leadership, thereby contributing to the development of character-based and value-oriented educational management models.